Phytoplasmas infecting pome and stone fruits in South America and Iberian peninsula - Quiroga, Nicolás (2018)
The present review focuses on the diseases associated with phytoplasmas that affect pome and stone fruits trees in Argentina, Bolivia, Chile, Uruguay, Spain and Portugal. The advances and challenges faced by these countries for these diseases are reported. The economic losses due to the presence of these bacteria seriously affect and reduce the production and the quality of the fruits.